Ethyl acetate detection using mixed-phase In2O3 nanorods - Santos, Gustavo Sanghikian Marques dos [UNESP]; Theodoro, Reinaldo dos Santos [UNESP]; Gera, Gabriela Oliveira; Perfecto, Tarcísio Micheli; Volanti, Diogo Paschoalini [UNESP] (American Chemical Society (ACS), 2025)
Detecting microbial volatile organic compounds (MVOCs) is critical for public health and food quality control applications but often requires complex analytical approaches. Ethyl acetate, an MVOC produced during the fermentation of bread and beer by Saccharomyces cerevisiae, holds significance in food quality control. Semiconductor metal oxides, particularly In₂O₃, are promising materials for MVOC sensing due to their cost-effectiveness, stability, and tunable sensing properties at the nanoscale. Enhanced sensing performance can be achieved by engineering heterostructures combining cubic and rhombohedral phases of In₂O₃ nanorods. In this work, In₂O₃ nanorods were synthesized via microwave-assisted hydrothermal method followed by calcination at 600, 500, and 400 °C to obtain single-phase cubic (In₂O₃-600) and mixed-phase cubic-rhombohedral (In₂O₃-500 and In₂O3-400) structures. The In₂O₃-500 heterostructure nanorods exhibited an enhanced response of 548 to ethyl acetate at 350 °C in dry air. It also showed a fast response time (1.8 s), a selectivity ratio of 2.1, and a theoretical detection limit of 525 ppb. Moreover, the material maintained a high response under 90% relative humidity (RH), demonstrating robustness under realistic operating conditions. These findings can be attributed to the synergistic effect of heterojunctions formed between the cubic and rhombohedral phases at the nanoscale, providing numerous active sites and defect-driven reactivity. The post-mortem characterization of the nanorod sensor was conducted using transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) to assess the long-term stability of the material.

A detecção de compostos orgânicos voláteis microbianos (MVOCs) é essencial para aplicações relacionadas à saúde pública e ao controle de qualidade de alimentos, mas geralmente requer abordagens analíticas complexas. O acetato de etila, um MVOC produzido durante a fermentação de pão e cerveja por *Saccharomyces cerevisiae*, possui relevância no controle de qualidade de alimentos. Os óxidos metálicos semicondutores, em especial o In₂O₃, são materiais promissores para a detecção de MVOCs devido ao seu baixo custo, estabilidade e propriedades sensoriais ajustáveis em escala nanométrica. O desempenho sensor aprimorado pode ser alcançado por meio da engenharia de heteroestruturas que combinem as fases cúbica e romboédrica de nanobastões de In₂O₃. Neste trabalho, nanobastões de In₂O₃ foram sintetizados pelo método hidrotérmico assistido por micro-ondas, seguido de calcinação a 600, 500 e 400 °C, a fim de obter estruturas de fase única cúbica (In₂O₃-600) e de fase mista cúbica-romboédrica (In₂O₃-500 e In₂O₃-400). A heteroestrutura de nanobastões In₂O₃-500 apresentou uma resposta aprimorada de 548 para acetato de etila a 350 °C em ar seco. Também exibiu um tempo de resposta rápido (1,8 s), uma razão de seletividade de 2,1 e um limite teórico de detecção de 525 ppb. Além disso, o material manteve alta resposta sob 90% de umidade relativa (UR), demonstrando robustez em condições reais de operação. Esses resultados podem ser atribuídos ao efeito sinérgico das heterojunções formadas entre as fases cúbica e romboédrica em escala nanométrica, que fornecem numerosos sítios ativos e reatividade induzida por defeitos. A caracterização pós-teste do sensor de nanobastões foi realizada por microscopia eletrônica de transmissão (TEM) e microscopia eletrônica de transmissão de alta resolução (HRTEM), para avaliar a estabilidade de longo prazo do material.
Detecção de acetato de etila usando nanobastões de In₂O₃ de fase mista
Keywords: Gas sensor; Post-mortem; Indium oxide; Ethyl acetate; Cubic-rhombohedral; Nanorods